Clerical Poverty in Early Sixteenth-Century England: Some East Anglian Evidence - Pound, John (The journal of ecclesiastical history, 1986)
The economic standing of the English parochial clergy in the early sixteenth century has been re-examined recently by Michael Zell, and the evidence at his disposal suggests that many of them were poverty-stricken in the extreme. He points to the large surplus of unendowed curates, chaplains and the like, and to the fact that when employment was available it was neither rewarding, in a monetary sense, nor necessarily secure. Stipends were officially regulated by an early fifteenth-century statute which set a maximum of £5 6s. 8d. per annum, and ‘evidence from all regions of England indicates that very rarely were curates and chaplains given more than that’. It was not uncommon for areas in the north to pay even less than this. In Lancashire, for example, the average salary of about 100 curates and chaplains in 1524 was £2 9s. 6d. In the East Riding of Yorkshire a year later it was £4. On the basis of such evidence, Mr Zell reasonably concludes that the unbeneficed clergy must have found it very difficult to survive, and that ‘the average country priest could not have been a person of high social status’.